PENGARUH EDUKASI FARMASI TERHADAP TINGKAT PENGETAHUAN PASIEN TENTANG OBAT SENDI DI APOTEK ESA GEMILANG KOTA PALOPO - Ricky Aditya Syam (Forind Press, 2026)
The background of this problem is the high incidence rate of joint disorders and the low understanding of patients towards treatments that risk triggering fatal complications. Therefore, the purpose of this study is to evaluate the influence of pharmaceutical education on patients' level of knowledge about joint medicine. This research was carried out in May–June 2025. This research method uses a pre-experimental quantitative approach with a pretest and posttest design of one group. Samples were taken through the saturated sampling technique, involving 42 patients at the Esa Gemilang Pharmacy, Palopo City. Data was collected using a standardized questionnaire and analyzed through the Paired Samples t-test. The results of the study showed a statistically significant increase in knowledge. Before the intervention, as many as 57.1 percent of patients had low knowledge, but after being given two-way participatory education based on visual media, 85.7 percent of patients managed to achieve a high level of knowledge with a significance value of 0.000 and an average difference of -2.452. In conclusion, pharmaceutical education interventions are significantly effective in improving patient health literacy. The researcher suggested that pharmacy services integrate interactive communication approaches and understanding screening as routine operational standards to optimize clinical outcomes.